KONTRIBUSI IQ (INTELLIGENCE QUOTIENT) DAN EQ (EMOTIONAL QUOTIENT) TERHADAP HASIL BELAJAR KOGNITIF BIOLOGI SISWA KELAS X SMA NEGERI 7 SURAKARTA TAHUN PELAJARAN 2011/2012 - Fatimah, Siti; Karyanto, Puguh; Rosyidi, Alvi (P Biologi FKIP UNS Surakarta, 2012)
ABSTRACT ? This research is aimed to know relationship between: 1) IQ (Intelligence Quotient) and cognitive learning achievement of biology of first student?s grade of SMA Negeri 7 Surakarta in academic year of 2011/2012, 2) EQ (Emotional Quotient) and cognitive learning achievement of biology of first student?s grade of SMA Negeri 7 Surakarta in academic year of 2011/2012, 3) IQ (Intelligence Quotient), EQ (Emotional Quotient), and cognitive learning achievement of biology of first student?s grade of SMA Negeri 7 Surakarta in academic year of 2011/2012. This was a correlational research. The population were all of the students first grade of SMA Negeri 7 Surakarta in academic year of 2011/2012. The sample was taken among 74 samples of student using simple random sampling technique. Documentation technique was used to uncover student?s cognitive learning achievement, while IQ (Intelligence Quotient) dan EQ (Emotional Quotient) was measured by using test technique. The obtained data was analysed using linier regression analysis in SPSS 17. The result showed that (1) there is correlation IQ (Intelligence Quotient) and cognitive learning achievement of biology of first student?s grade of SMA Negeri 7 Surakarta in academic year of 2011/2012, 2) there is correlation EQ (Emotional Quotient) and cognitive learning achievement of biology of first student?s grade of SMA Negeri 7 Surakarta in academic year of 2011/2012, 3) there is correlation both of IQ (Intelligence Quotient) and EQ (Emotional Quotient) with cognitive learning achievement of biology of first student?s grade of SMA Negeri 7 Surakarta in academic year of 2011/2012. The three aforementioned correlation are considered as significant and positive valuable. In addition the results showed that relative contribution of IQ toward cognitive learning achievement in Biology is 48.6%, relative contribution of EQ toward cognitive learning achievement in Biology is 51.4%, Effective contribution of IQ toward cognitive learning achievement in Biology is 7.63%, effective contribution of EQ toward cognitive learning achievement in Biology is 8.07%, total effective contribution both of IQ and EQ are15.7% Keywords: IQ (Intelligence Quotient), EQ (Emotional Quotient),cognitive learning achievement in biology, linier regression analysis